1995
DOI: 10.1007/bf00931538
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofEntamoeba histolytica intracellular phospholipase A and lysophospholipase L1 activities

Abstract: Entamoeba histolytica phospholipase A and lysophospholipase activities from a vesicular subcellular fraction (P30) were analyzed. The products, obtained using specific substrates labeled with 14C or 3H, indicated the presence of phospholipase A1 and A2 as well as lysophospholipase L1 activities. The enzymes detected could participate in phospholipid metabolism and the alkaline phospholipase A2 may contribute to E. histolytica cytopathogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…We have demonstrated the presence of phospholipases in Trichomonas [21], amoeba [46], and giardia [47]. But the presence of sphingomyelinases has not been described in T. vaginalis.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated the presence of phospholipases in Trichomonas [21], amoeba [46], and giardia [47]. But the presence of sphingomyelinases has not been described in T. vaginalis.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of PGs is not yet well understood. The cycle of transformation begins with phospholipase A 2 , the enzyme whose presence in the lysosomes of protozoa has been established (Visvevara and Balamuth 1975; Misra et al 1983;Vargas-Villarreal et al 1995). The synthesis of PGs begins with the enzyme known as the synthase of endoperoxides of PGs (E.C.…”
Section: Discussionmentioning
confidence: 99%
“…The spots belonging to PC, LPC and FFA were identified. These lipids were recovered by scalpel scraped of each sample from the plates, and their radioactivity determined (expressed as disintegrations per min, DPM) as described elsewhere (Vargas-Villarreal et al 1995). All determinations were performed in triplicate and presented as mean ± SE.…”
Section: Sequence Of T Vaginalis Phospholipase 521mentioning
confidence: 99%
“…These enzymes are important in the pathogenic mechanisms of the protozoa such as T. vaginalis , 2005, Lubick and Burgess 2004, Entamoeba histolytica (Long-Krug et al 1985;Vargas-Villarreal et al 1995González-Garza et al 2000), Trypanosoma cruzi (Wainszelbaum et al 2001), and Naegleria fowleri (Barbour and Marciano-Cabral 2001). We have previously shown that the P30 and S30 subcellular fractions of T. vaginalis incubated in presence of human or rat erythrocytes.…”
Section: Introductionmentioning
confidence: 99%